Working Capital Management and Managerial Performance in some Selected Manufacturing Firms in Edo State Nigeria - Orumwense, Jones Osasuyi; Mwakipsile, Greenfield (Journal of Accounting, Business and Finance Research, 2017)
This study was conducted to correlate working capital Management’s impact to Managerial Performance in Some selected Manufacturing Firms in Edo State Nigeria. The study was conducted through descriptive survey and correlation research design, quantitative approach with a questionnaire and include 100 respondents derived from a target population of 134 from the selected manufacturing firms in Edo State Nigeria. The research found that the working capital Management and Managerial Performance of the selected manufacturing firms are significantly correlated. The Selected Manufacturing Firms should separate responsibilities of receiving, recording, and storing of goods, if not material assets lost or vandalized. Also, the selected manufacturing firms are advised to capitalized on the policies they adopt which were rated as satisfactory or very satisfactory.